Pendampingan Manajemen Administrasi, Pemasaran Sebagai Pengembangan Kinerja Bisnis UMKM Sego Babat Bos Empok: Penelitian - Friska Dini Margareta; Almas Nurul Jannah; Reni Dwi Saputri; Jennifer Farihadul Bait (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in strengthening the community's economy. However, many business actors still face obstacles in administration, legality, finance, and marketing. The Sego Babat Bos Empok MSME, which operates in the culinary sector, has the potential to grow but does not yet have a Business Identification Number (NIB), its finances are still manual, and its marketing is still not optimal. This community service activity aims to provide comprehensive assistance through observation, interviews, outreach, and direct assistance. The administration sector is carried out by registering the NIB through the Online Single Submission (OSS). The finance department provides assistance with the Kasir Pintar application to facilitate business financial recording. Then the marketing sector is strengthened through social media management by creating attractive promotional content. The results of the assistance show an understanding of business legality, more organized financial records, and more attractive digital promotions that can increase the competitiveness of MSMEs.